The Montessori’s Values in Teaching English to Young Learners (TEYL) - Aprilian Ria Adisti (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2018)
Teaching English to Young Learner (TEYL) becomes so popular today since the needs of facing globalization era. The Montessori Method one of the best educational methods for children based on the child development theory of Dr. Maria Montessori. The essence of the Montessori Method is to make the child an independent learner. This research uses descriptive qualitative method which aims to describe the implementation of Montessori’s values into Teaching English to Young Learners at Aisyiyah Kindergarten, Karanganyar. The subjects of this research are English teacher and 26 students in this school. Based on the results of the research, it was concluded that the application of Montessori's values in TEYL is able to increase students' interest and enthusiasm in learning English.